Characterization of unique B-cell populations in the circulation of people living with HIV prior to non-Hodgkin lymphoma diagnosis - Martínez, Laura E.; Comin-Anduix, Begoña; Güemes-Aragon, Miriam; Ibarrondo, Javier; Detels, Roger; Mimiaga, Matthew J.; Epeldegui, Marta (Frontiers in Immunology, 2024)
People living with HIV (PLWH) are at higher risk of developing lymphoma. In this study, we performed cytometry by time-of-flight (CyTOF) on peripheral blood mononuclear cells of cART-naïve HIV+ individuals and cART-naïve HIV+ individuals prior to AIDS-associated non-Hodgkin lymphoma (pre-NHL) diagnosis. Participants were enrolled in the Los Angeles site of the MACS/WIHS Combined Cohort Study (MWCCS). Uniform Manifold Approximation and Projection (UMAP) and unsupervised clustering analysis was performed to identify differences in the expression of B-cell activation markers and/or oncogenic markers associated with lymphomagenesis. CD10+CD27- B-cells, CD20+CD27- B-cells, and B-cell populations with aberrant features (CD20+CD27+CXCR4+CD71+ B-cells and CD20+CXCR4+cMYC+ B-cells) were significantly elevated in HIV+ cART-naïve compared to HIV-negative samples. CD20+CD27+CD24+CXCR4+CXCR5+ B-cells, CD20+CD27+CD10+CD24+CXCR4+cMYC+ B-cells, and a cluster of CD20+CXCR4hiCD27-CD24+CXCR5+CD40+CD4+AICDA+ B-cells were significantly elevated in HIV+ pre-NHL (cART-naïve) compared to HIV+ cART-naïve. A potentially clonal cluster of CD20+CXCR4+CXCR5+cMYC+AICDA+ B-cells and a cluster of germinal center-B-cell-like cells (CD19-CD20+CXCR4+Bcl-6+PD-L1+cMYC+) were also found in circulation of HIV+ pre-NHL (cART-naïve). Moreover, significantly elevated clusters of CD19+CD24hiCD38hi cMYC+ AICDA+ B regulatory cells were identified in HIV+ pre-NHL (cART-naïve) compared to HIV+ cART-naïve. The present study identifies unique B-cell subsets in PLWH with potential pre-malignant features that may contribute to the development of pre-tumor B-cells in PLWH and that may play a role in lymphomagenesis.